PASAR MODAL SYARIAH (PMS) DI INDONESIA - Muhammad Ridwansyah ME (Jurnal Ekonomi Bisnis Syariah, 2019)
In this journal the main topics of discussion include how is the scope of the Islamic capital market, how is the legal basis and contract in the operations of the Islamic capital market and how is the development of the Islamic capital market in Indonesia. Securities trading, public companies related to securities issued and institutions and professions related to securities that carry out their activities in accordance with sharia principles, the legal basis of conventional capital market operations as already stated, have not applied the principles of sharia. Thus, the legal basis for the application of sharia principles for PMS operations is based on six DSN-MUI fatwas relating to the capital market industry. Six DSN-MUI Fatwas related to the capital market industry include: (1) fatwa no. 5/2000 concerning Sale and Purchase Greetings, (2) fatwa no. 20/2000 concerning Investment Implementation Guidelines for Sharia Mutual Funds, (3) fatwa no. 32/2002 concerning Sharia Bonds, (4) fatwa no. 33/2002 concerning Mudharabah Syariah Bonds, (5) fatwa no. 40/2003 concerning Capital Markets and General Guidelines on the Application of Sharia Principles in the Capital Market Sector, and (6) fatwa no. 41/2004 concerning Ijarah Sharia Bonds. Whereas PMS in Indonesia can still follow the PMK which prioritizes capitalism and materialist attitudes. This is because capital market players only cover a very small number of people compared to the whole Indonesian people. However, the small number of people who roll out fantastic investments, can reach trillions of rupiah every day. In addition, the basic values ​​of the Islamic Economic System, namely balance, fairness, and ownership by experts, have not yet penetrated the dynamics and determination of market participants in PMS.